Retrospective analysis of 51 intralesionally treated cases with progressed giant cell tumor of the bone: local adjuvant use of hydrogen peroxide reduces the risk for tumor recurrence - Omlor, Georg; Lange, Jessica; Streit, Marcus R.; Gantz, Simone; Merle, Christian; Germann, Thomas; Mechtersheimer, Gunhild; Fellenberg, Jörg; Lehner, Burkhard (World journal of surgical oncology, 2019)
Giant cell tumor of the bone (GCT) has high local recurrence rates and the prognosis is hard to predict. We therefore retrospectively analyzed clinical outcome and recurrences of 51 GCT cases focusing on the effects of adjuvant local use of hydrogen peroxide.